2005
DOI: 10.1111/j.1365-2796.2005.01558.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral B lymphocyte β1,3‐galactosyltransferase and chaperone expression in immunoglobulin A nephropathy

Abstract: . Purpose.  Aberrant O‐glycosylation of serum IgA1 is presumed to be one of the main pathogenesis of immunoglobulin A nephropathy (IgAN). β1,3‐galactosyltransferase (β1,3GT), whose activity requires coexistence of a specific chaperone, is the main enzyme which participate in the glycosylation process. The current study was carried out to elucidate the expression level of β1,3GT (C1GALT1) and its chaperone (Cosmc) in IgAN, and their relationships with clinical features as well as IgA glycosylation level. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 27 publications
4
65
0
1
Order By: Relevance
“…In IgAN, IgA1 seems to be undergalactosylated, leading to increased exposure of terminal GalNAc. Defective expression or function of C1Gal-T has been suggested as a basis for this, and, more recently, underexpression of the chaperone protein Cosmc by peripheral blood cells has been demonstrated (25). However, altered IgA1 O-galactosylation cannot be attributed fully to a straightforward lack of galactosylating activity in affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In IgAN, IgA1 seems to be undergalactosylated, leading to increased exposure of terminal GalNAc. Defective expression or function of C1Gal-T has been suggested as a basis for this, and, more recently, underexpression of the chaperone protein Cosmc by peripheral blood cells has been demonstrated (25). However, altered IgA1 O-galactosylation cannot be attributed fully to a straightforward lack of galactosylating activity in affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The stability and activity of this enzyme depends on a chaperone, Cosmc (25). Transcription of Cosmc has also been found to be reduced in IgAN patients (43). Mutations of this protein result in the production of Galdeficient O-linked glycans in Tn syndrome, a rare disease formerly called permanent mixed-field polyagglutinability, which is characterized by thrombocytopenia, leukopenia, and hemolytic anemia, but not nephritis (26, 44-46).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that B cells in the circulation of IgAN patients have lower expression and/or show less activity of β1,3-galactosyltransferase than such cells in healthy controls (42,43). The stability and activity of this enzyme depends on a chaperone, Cosmc (25).…”
Section: Discussionmentioning
confidence: 99%
“…The IgA1 in the circulation of patients with IgAN also carries Galdeficient O-glycans, although Gal-deficient variants are rarely found in the IgA1 in sera from normal individuals (7)(8)(9)15). The production of these variants is due to altered expression of specific glycosyltransferases in the IgA1-producing cells (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%